2012
DOI: 10.1038/mp.2012.143
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of alcohol-dependence symptom counts in extended pedigrees identifies C15orf53

Abstract: Several studies have identified genes associated with alcohol use disorders, but the variation in each of these genes explains only a small portion of the genetic vulnerability. The goal of the present study was to perform a genome-wide association study (GWAS) in extended families from the Collaborative Study on the Genetics of Alcoholism (COGA) to identify novel genes affecting risk for alcohol dependence. To maximize the power of the extended family design we used a quantitative endophenotype, measured in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 45 publications
2
85
0
Order By: Relevance
“…The genetic contribution to vulnerability to develop alcohol or drug dependence has generally been estimated in the range 40-70%, depending on the substance, consistent with complex inheritance in which multiple genes exert a small effect of vulnerability or protection, A genetic meta-analysis D Li et al along with the environment (Frank et al, 2012;Gelernter and Kranzler, 2009;Goldman et al, 2005;Heath et al, 2011;Kendler et al, 2007;Wang et al, 2013). By analyzing potential associations between specific alleles and multiple substance phenotypes, our analyses may represent a necessary step toward identifying the effects of phenotypeinfluencing genes with improved certainty.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic contribution to vulnerability to develop alcohol or drug dependence has generally been estimated in the range 40-70%, depending on the substance, consistent with complex inheritance in which multiple genes exert a small effect of vulnerability or protection, A genetic meta-analysis D Li et al along with the environment (Frank et al, 2012;Gelernter and Kranzler, 2009;Goldman et al, 2005;Heath et al, 2011;Kendler et al, 2007;Wang et al, 2013). By analyzing potential associations between specific alleles and multiple substance phenotypes, our analyses may represent a necessary step toward identifying the effects of phenotypeinfluencing genes with improved certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Using a symptom count phenotype, Wang et al . 15 identified a significant association of AD with C15orf53 .…”
Section: Introductionmentioning
confidence: 96%
“…A potential future challenge might be posed by the change in diagnostic criteria with the publication of DSM-V [6]. While merging the diagnostic criteria into a single entity ‘substance use disorders' with varying degrees of severity might ease the definition of endophenotypes or of semiquantitative approaches like symptom count [176], great care must be taken when comparing studies based on DSM-V with previously published DSM-IV-based work. Also, GxE interactions must be considered [189,190,191], although keeping in mind that the GxE approach is one of the most challenging and complex of all conceptual frameworks applied in the genetic investigation of AUDs [197].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…A potential endophenotype solely based on clinical criteria is the symptom count as a crude, but straightforward measure of disease severity that can be applied in both patients and healthy controls. In a GWAS directed at alcohol dependence symptom count, Wang et al [176] found converging evidence for a role of the thus far poorly characterized C15ORF53 gene in the etiology of alcohol dependence-related phenotypes. Other endophenotypes show a weaker statistical association with the clinical phenotype of interest, but might be more directly related to the underlying pathophysiological mechanisms.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%